2014
DOI: 10.1177/0003319714532168
|View full text |Cite
|
Sign up to set email alerts
|

Which Calculation Method of Glomerular Filtration Rate is Suitable in Patients With Normal or Mildly Impaired Renal Function?

Abstract: We read the article entitled ''Association of Glomerular Filtration Rate With Slow Coronary Flow in Patients With Normal to Mildly Impaired Renal Function'' by Akin et al 1 with interest. The authors 1 concluded that estimated glomerular filtration rate (eGFR) was significantly correlated with slow coronary flow in patients with normal to mildly impaired kidney function.The Kidney Disease: Improving Global Outcomes organization developed clinical practice guidelines 2 in 2012, recommending that the Chronic Kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…In addition, it was determined that this equation overcame the limitation of the MDRD equation (i.e., the underestimation of GFR at given range). [17][18][19][20] Stevens LA et al [20] showed that bias was substantially decreased with the CKD-EPI equation, compared to measured GFR, particularly among people with eGFR greater than 60 ml/min/1.73 m 2 . The study also found that bias was increased using the MDRD equation, when eGFR was greater than 90 ml/min/1.73 m 2 .…”
Section: Is There a Relationship Between Slow Coronary Flow And Normamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was determined that this equation overcame the limitation of the MDRD equation (i.e., the underestimation of GFR at given range). [17][18][19][20] Stevens LA et al [20] showed that bias was substantially decreased with the CKD-EPI equation, compared to measured GFR, particularly among people with eGFR greater than 60 ml/min/1.73 m 2 . The study also found that bias was increased using the MDRD equation, when eGFR was greater than 90 ml/min/1.73 m 2 .…”
Section: Is There a Relationship Between Slow Coronary Flow And Normamentioning
confidence: 99%
“…According to the Kidney Disease: Improving Global Outcomes (KDIGO) 2012 guideline, the CKD-EPI equation provides less bias than the MDRD equation, as well as improved risk stratification, [16] and recent studies have confirmed these findings. [17][18][19][20] In the present study, eGFR values in patients with normal coronary flow (NCF) and SCF, who had near-normal or mildly impaired renal function were compared using the CKD-EPI and MDRD equations. The present study was the first to evaluate this relationship with the CKD-EPI equation.…”
mentioning
confidence: 99%
“…We thank Cabuk et al 1 for their comments. 2 They raise concerns about the equation used for reporting estimated glomerular filtration rate (eGFR) in our study and how this could impact on our results.…”
mentioning
confidence: 97%
“…Cabuk et al 1 wanted to clarify the possible factors that can influence the creatinine levels and eGFR in our study. Patients with altered muscle mass (eg, reduced by amputation, paraplegia, immobilization, or a neuromuscular disorder and increased by dietary protein intake or creatine dietary supplements) were excluded from our study.…”
mentioning
confidence: 99%
See 1 more Smart Citation